(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
This paper brings together Ursula K. Le Guin’s novel Always Coming Home and Biljana Crvenkovska’s novel Куќа над Брановите (House Above the Waves) by reading the Macedonian text in relation to Arne Næss’s theory of deep ecology and in the broader context of Le Guin’s ecological poetics. These novels represent different literary traditions, cultures, and histories, but articulate ideas of "dwelling": not as just shelter, but as a way of living with the natural world. Whereas Le Guin has long been discussed in feminist and ecocritical circles, Crvenkovska’s work, published recently, has so far received limited critical attention beyond local cultural commentary. This paper examines House Above the Waves through the lens of deep ecology, showing how its stripped-down style reflects on the value of nature and the shifting boundaries between body, self, and environment. Considering the novel in relation to Le Guin’s work allows us to see how deep ecological ideas emerge across distinct literary traditions—whether in communal ritual or in solitary endurance. Both stories offer meaningful ways to rethink how we live as part of a more-than-human world.